2012
DOI: 10.1111/j.1438-8677.2012.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Myrosin cells’ are not a prerequisite for aphid feeding on oilseed rape (Brassica napus) but affect host plant preferences

Abstract: The enzyme myrosinase (EC 3.2.3.1.147) is present in specialised myrosin cells and forms part of the glucosinolate-myrosinase system, also known as 'the mustard oil bomb', which has an important role in the defence system of cruciferous plants against insect pests. Transgenic Brassica napus MINELESS have been produced by transgenic ablation of myrosin cells. This prompted us to investigate the importance of myrosin cells in plant-aphid interactions. In order to study this, we challenged transgenic MINELESS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
0
14
0
1
Order By: Relevance
“…In this study, the total glucosinolate levels were observed to be higher in MINELESS control seedlings relative to wild-type control seedlings. Moreover, in our previous studies, we have shown the total glucosinolate levels to be higher in MINELESS control (non-infested) seeds than wild-type control seeds and seedlings ( Borgen et al , 2010 ; Ahuja et al , 2011 ; Borgen et al , 2012 ). Glucosinolates form a constitutive defence ( Wittstock and Gershenzon, 2002 ), but it is also evident that these compounds accumulate in response to wounding or herbivory ( Doughty et al , 1995 ; Bartlet et al , 1999 ; Brader et al , 2001 ; Mikkelsen et al , 2003 ).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In this study, the total glucosinolate levels were observed to be higher in MINELESS control seedlings relative to wild-type control seedlings. Moreover, in our previous studies, we have shown the total glucosinolate levels to be higher in MINELESS control (non-infested) seeds than wild-type control seeds and seedlings ( Borgen et al , 2010 ; Ahuja et al , 2011 ; Borgen et al , 2012 ). Glucosinolates form a constitutive defence ( Wittstock and Gershenzon, 2002 ), but it is also evident that these compounds accumulate in response to wounding or herbivory ( Doughty et al , 1995 ; Bartlet et al , 1999 ; Brader et al , 2001 ; Mikkelsen et al , 2003 ).…”
Section: Discussionmentioning
confidence: 73%
“…6 ), which were 36.5- and 38.8-fold higher in the MINELESS control compared to the wild-type control. The detection of high amounts of these compounds particularly in MINELESS seedlings is interesting as we have not found these compounds before in MINELESS seeds or seedlings ( Borgen et al , 2010 ; Ahuja et al , 2011 ; Borgen et al , 2012 ). 1 MTPe has been detected in B .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Transgenic OSR has been produced with low myrosinase activity (Borgen et al 2010) which consequently reduces the production of glucosinolate hydrolysis products (mainly isothiocyanates). Compared to wild-type, these low isothiocyanate releasing seedlings were more preferred in free-choice experiments by generalist aphid species but less preferred by specialist aphid species (Borgen et al 2012). However, such manipulation of plant volatile emissions can result in physiological costs to the plant (Robert et al 2013) and it is imperative that any modifications do not impair the plant's natural ability to defend itself against other generalist pests after herbivore attack (Hopkins et al 2009).…”
Section: Semiochemical Control Optionsmentioning
confidence: 99%
“…For example, related plants often share a similar composition of secondary metabolite, such as the glucosinolates of Brassicaceae and relatives (Spencer , Borgen et al. ). In addition, plant phylogeny may be correlated with other life‐history traits.…”
Section: Introductionmentioning
confidence: 99%